Factors That Influence Diabetes Disease: Case Study: Pima Indians - Ni Made Deviani Prisilia; Adelia Yuniarti; Citra Annisa Rahmania; Made Ayu Asri Oktarini Putri; Made Susilawati (International Journal of Applied Mathematics and Computing, 2024)
Diabetes is one of the non-communicable diseases that is considered dangerous due to its susceptibility to complications. This disease is caused by high blood sugar levels in a person's body, which makes the blood more alkaline and slows down the metabolic process. In this study, we observed 8 variables that are considered influential in diabetes and will build a regression model that can predict the response variable (y) through Logistic Regression Analysis. Logistic Regression Analysis is a statistical analysis method used to describe the relationship between a dependent variable with two or more categories and one or more independent variables that are categorical or continuous. Based on the results, the logistic regression model for factors influencing diabetes in the Indian Pima tribe includes variables such as number of pregnancies, glucose level, blood pressure, body mass index, and diabetes pedigree function